ANALISIS PROGRAM PELATIHAN GURU UNTUK MENINGKATKAN KOMPETENSI PROFESIONAL: Development and analysis of a blended learning–based, lesson study, and professional learning community training program for vocational school teachers to enhance professional competence - Saepuloh, Toyib; Nugraha, Mulyawan Safwandy (Perkumpulan Peneliti dan Pegiat Literasi, 2025)
Teacher professional development in vocational schools remains a challenge in Indonesia, particularly in integrating technology, project-based learning (PjBL), and reflective practices into teaching. This study examined the effectiveness of an integrative training model combining blended learning, lesson study, reflective practice, and professional learning communities (PLC) in improving teachers’ competence and its impact on students. Using a mixed-methods approach, data were collected from 28 teachers and 245 students at SMK PGRI Karisma Bangsa through pre- and post-tests, interviews, observations, and document analysis. Results showed significant improvements in educational technology (62.5 to 80.4), PjBL (59.7 to 77.8), and interactive media development (58.9 to 81.2) (p < 0.001). Qualitative findings revealed higher teacher confidence, stronger reflective skills, and sustained collaboration through PLC. Students perceived classes as more engaging (76%), easier to understand (69%), and more relevant to workplace contexts (64%). These findings confirm previous studies on blended learning and PjBL, but add novelty by integrating four approaches simultaneously. The study suggests reflective-collaborative dimensions should complement the TPACK (Technological Pedagogical Content Knowledge) framework to sustain teacher competence and offers a scalable model for vocational teacher training.